Bat intrusions at a tertiary care center in Iowa, 2018–2020. (16th December 2022) - Alsuhaibani, Mohammed A.; Dains, Angelique; Kobayashi, Takaaki; Sheeler, Lorinda L.; Trannel, Alexandra; Holley, Stephanie; Marra, Alexandre R.; Abosi, Oluchi J.; Jenn, Kyle E.; Meacham, Holly; Etienne, William; Kukla, Mary E.; et al.
Abstract: We described the epidemiology of bat intrusions into a hospital and subsequent management of exposures during 2018–2020. Most intrusions occurred in older buildings during the summer and fall months. Hospitals need bat intrusion surveillance systems and protocols for bat handling, exposure management, and intrusion mitigation.